1996
DOI: 10.1002/(sici)1097-0010(199609)72:1<8::aid-jsfa646>3.3.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Performance, Water Use and Effluent Output of Weaner Pigs Fed ad libitum with Either Dry Pellets or Liquid Feed and the Role of Microbial Activity in the Liquid Feed

Abstract: Forty eight and ninety six pigs weaned at 22.6 f 2.6 days, were allocated to two trials to study the effect of feeding post-weaning diets ad libitum, either as dry pellets (DF) or as meal mixed with water in the ratio 2.5 : 1 (LF). The trials, lasting 28 days, differed only in the type of trough used to present the liquid feed to the pigs. In both trials the daily gain of LF pigs over the 4 weeks of the trial was significantly ( P < 0.001) better than that of the D F pigs. Daily gains for the two treatment gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 0 publications
1
45
0
1
Order By: Relevance
“…However, coliform bacteria proliferated in the FLF (Table 1). Other investigations have shown that coliform bacteria are suppressed in FLF Russel et al, 1996;Mikkelsen and Jensen, 1997). The presence of coliform bacteria in the FLF may be an explanation for the relatively poorer growth performance of piglets fed the FLF in the present study (Table 2).…”
Section: Methodsmentioning
confidence: 93%
“…However, coliform bacteria proliferated in the FLF (Table 1). Other investigations have shown that coliform bacteria are suppressed in FLF Russel et al, 1996;Mikkelsen and Jensen, 1997). The presence of coliform bacteria in the FLF may be an explanation for the relatively poorer growth performance of piglets fed the FLF in the present study (Table 2).…”
Section: Methodsmentioning
confidence: 93%
“…Lactobacillus spp. have been found to proliferate rapidly during the first days of the fermentation of pig feed, after which fairly constant numbers are maintained (10,12,20,28). However, identifying yeasts and LAB to the species level demonstrated substantial changes within these apparently stable populations.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, piglets had almost no advantage of consuming the diet as FLF, as mostly the supernatant water part, especially in the beginning of the experiment, was consumed (Figure 2). The trough design is one of the possible reasons for the worse performance of the piglets on FLF (Russell et al 1996). More feed wastage was noted by piglets fed FLF compared with piglets fed a dry diet.…”
Section: Experiments IImentioning
confidence: 99%